2014
DOI: 10.1007/s13193-014-0290-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cyclooxygenase 2 (COX-2) in Prognosis of Breast Cancer

Abstract: COX-2 regulates tumour growth, invasion and metastasis in breast cancer. This study investigated the association between COX-2 expression in human breast cancer versus the expression of ER, PR, HER-2/neu, as well as its association with other established prognostic indicators like age, menopausal status, tumour size, lymph nodal status, stage, grade, NPI and histological subtype, and aims to validate the role of overexpression of COX-2 as a prognostic marker in patients with breast cancer in Indian subcontinen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 28 publications
5
46
1
Order By: Relevance
“…In our observational study, treatment with 500 µmol/l NaHS for 24 h obviously promoted protein COX-2 secretion in PLC/PRF/5 hepatoma cells. Importantly, accumulating evidence has demonstrated that cyclooxygenase (COx)-2 is overexpressed in several types of cancers cells (73)(74)(75) including hepatocellular carcinoma (HCC) (76). COX-2 expression in cells and animal models is closely associated with tumor cell growth and is a crucial molecule in the development of malignant tumors, including promotion of angiogenesis (77), anti-apoptotic effects (78), invasiveness of tumor cells (74), and tumor cell proliferation (79), demonstrating that COX-2 pathway is implicated in NaHS-induced PLC/PRF/5 hepatoma cell proliferation, anti-apoptosis, angiogenesis and migration.…”
Section: Discussionmentioning
confidence: 99%
“…In our observational study, treatment with 500 µmol/l NaHS for 24 h obviously promoted protein COX-2 secretion in PLC/PRF/5 hepatoma cells. Importantly, accumulating evidence has demonstrated that cyclooxygenase (COx)-2 is overexpressed in several types of cancers cells (73)(74)(75) including hepatocellular carcinoma (HCC) (76). COX-2 expression in cells and animal models is closely associated with tumor cell growth and is a crucial molecule in the development of malignant tumors, including promotion of angiogenesis (77), anti-apoptotic effects (78), invasiveness of tumor cells (74), and tumor cell proliferation (79), demonstrating that COX-2 pathway is implicated in NaHS-induced PLC/PRF/5 hepatoma cell proliferation, anti-apoptosis, angiogenesis and migration.…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 expression was used to predict whether tumors were likely to metastasize or, in the case of ductal carcinoma in situ (DCIS), to recur. In a study of high-grade breast tumors, COX-2 expression was predictive for lymph node metastasis in tumors greater than 20 mm in size [59,60]. In DCIS, COX-2 expression was predictive for recurrence [68].…”
Section: Cox-2 Expression In Breast Cancermentioning
confidence: 99%
“…In several breast cancer studies examining COX-2 expression (mRNA and/or protein by immunohistochemistry), COX-2 was only expressed in tumor, not normal breast tissue, and overall its expression in tumors predicted a worse prognosis [59][60][61][62][63][64][65][66][67]. COX-2 expression was used to predict whether tumors were likely to metastasize or, in the case of ductal carcinoma in situ (DCIS), to recur.…”
Section: Cox-2 Expression In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…COX-2 is generally produced when the body suffers stimulation, and is involved in the inflammatory response (16). Studies have found an abnormal expression of COX-2 protein in several types of tumor tissues, which suggests that it may be involved in the tumorigenesis and the development and metastasis of cancer (17,18). iNOS is generally produced by macrophages or monocytes and is the main sign of an inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%